Ionic‐Liquid‐Assisted Hydrothermal Synthesis of Ag/AgBr for Photodegradation of Imidacloprid under Visible Light. Issue 5 (19th March 2019) - Guo, Dandan; Zhu, Xiaoqing; Chen, Sheyun; Wang, Cenling; Pi, Mingli; Chen, Xiaoxia; Shi, Yuqing; Dai, Jingtao
Abstract : Ag/AgBr photocatalysts are prepared by a ionic‐liquid‐assisted hydrothermal method. The as‐prepared photocatalysts are characterized by scanning electron microscopy, X‐ray powder diffraction, X‐ray photoelectron spectroscopy, Brunauer–Emmett–Teller measurement, and diffuse reflectance spectroscopy. Ag/AgBr exhibits significant photocatalytic activity toward degradation of imidacloprid under visible light. After 9 h, the conversion percentage of imidacloprid reaches 90%. Besides, the cycle performances suggest a good stability of the catalyst. The photocatalytic kinetics indicate that the degradation processes follow pseudo‐first‐order kinetics. According to the fact that electron holes OH and O2 − greatly promote the photodegradation process, the degradation mechanism is proposed. Abstract : A Ag/AgBr photocatalyst is prepared by ionic liquid (IL)‐assisted hydrothermal method and acts as a high‐performance and recyclable catalyst for efficient photocatalytic removal of imidacloprid under visible light. The possible visible‐light‐induced photocatalytic mechanism and the degradation pathway of intermediate products are also proposed.